Can CDM Deliver Its Emission Reduction Purpose? : a panel data analysis for developing countries - Karamik, Sule (SLU/Dept. of Economics, 2022)
The Clean Development Mechanism (CDM) is one of the three flexible mechanisms defined within the Kyoto Protocol. It aims to help developed countries achieve emission reduction targets with low abatement costs while providing sustainable development to developing countries. However, whether CDM has delivered this dual objective has been questionable. This study empirically examines the long-run effect of CDM projects on carbon dioxide emissions per capita for 69 eligible developing countries from 1993 to 2012 with a panel data analysis. The research mainly focuses on Pooled Mean Group (PMG) estimator that allows short-run coefficients to alter between groups but restricts long-run coefficients to be the same. The empirical results indicate a significant and positive relationship between CDM projects and carbon dioxide emissions per capita in the long run, implying that CDM did not lead to emission reductions in respective countries over 1993-2012. This result can be explained due to non-additional projects operated within the mechanism. To observe emission reductions with the implementation of CDM projects, we conclude that assessments regarding additionality and issued emission credits should be improved with better methodologies, governance and increased transparency.